2002
DOI: 10.1002/jctb.623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on microbial hydrogen fermentation

Abstract: The in¯uence of initial pH of the culture medium on hydrogen production was studied using sucrose solution and a mixed microbial¯ora from a soybean-meal silo. Hydrogen production was not observed at pH values of 3.0, 11.0 and 12.0 but low production was observed at pH values 5.0 and 5.5. The pH of the experimental mixture decreased rapidly and produced hydrogen gas within 30 h. Methane was not detected at initial pH values between 6.0 and 10.0. The sucrose degradation ef®ciency increased as the initial pH valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(74 citation statements)
references
References 25 publications
2
57
1
14
Order By: Relevance
“…The distribution of metabolites formed during H 2 fermentation is often a crucial signal in assessing the efficiency of H 2 -producing cultures. [22][23][24] At initial D of 4.5 days Ϫ1 (days 1-2), VFA concentration was higher than ethanol. Butyrate (45.2-49.7%) and acetate (12.9 -15.4%) were the two major components of VFAs in the first two days, though lactate composition was high on day 1.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of metabolites formed during H 2 fermentation is often a crucial signal in assessing the efficiency of H 2 -producing cultures. [22][23][24] At initial D of 4.5 days Ϫ1 (days 1-2), VFA concentration was higher than ethanol. Butyrate (45.2-49.7%) and acetate (12.9 -15.4%) were the two major components of VFAs in the first two days, though lactate composition was high on day 1.…”
Section: Methodsmentioning
confidence: 99%
“…The change of sludge pH values was caused by production of VFA and NH 4 + -N [21] . Unlike the hydrogen fermentation of carbohydrates [15] , the change of sludge pH value was unobvious. The maximal hydrogen production and hydrogen consumption occurred at certain pH value, which were different at different initial pH values.…”
Section: Effect Of Initial Ph On Hydrogen Productionmentioning
confidence: 99%
“…pH value is an important factor that affects the biological hydrogen production. The effect of pH value on the hydrogen production of carbohydrates has been studied by many researchers [13][14][15] . However, little work discussed the effect of pH even though it is really a critical factor ruling over the anaerobic reactions.…”
mentioning
confidence: 99%
“…The finding suggests that various organic wastes covering a wide range of pH values can be used for hydrogen fermentation without adjusting the initial pH. Lee et al [7] reported that hydrogen production yields were higher at high alkaline pH than lower pH conditions (pH from 5 to 8), suggesting that hydrogenase enzyme systems are functioned at high alkaline pH conditions. Hydrogen production yield in the initial pH 10 decreased with a long lag time, which could be due to the toxic effects of a high pH.…”
Section: Hydrogen Yield Under Various Phs Conditionmentioning
confidence: 99%
“…Lee et al [7] reported that the optimal initial pH for the biohydrogen fermentation of sucrose was 9.0. Cai et al [8] showed that the maximal hydrogen yield from sewage sludge occurred at an initial pH of 11.0.…”
Section: Introductionmentioning
confidence: 99%